30 Years of Research in Brand Personality: Mapping Knowledge and Analyzing the Thematic Structure by a Scientometrics Approach - Mohammad Rahim Esfidani; Mohsen Nazari; Shahriar Gharibzadeh; Nakisa Rezaie (‫مدیریت بازرگانی)
Objective Brands play a pivotal role in establishing connections with customers, transcending mere commercial transactions to foster sustainable and profitable relationships. These roles manifest themselves in functional, symbolic, and emotional domains, sometimes even evolving into emotional bonds between individuals and brands. Brand personality is considered a critical element in brand differentiation and positioning strategies. It has attracted significant attention from researchers and marketers over the past three decades, leading to numerous studies in this field. Given the increasing research in brand studies in recent years, with more researchers expected to focus on this area, a comprehensive analysis of its conceptual structure is of paramount importance. This study aims to review articles on brand personality published in reputable international journals and analyze publication trends to identify opportunities for future research.